Collection of materials on the experience of combat activities of the naval forces of the USSR : No. 2, experience of daytime submarine torpedo attacks. - Gebhardt, James R., translator (Directorate of the Naval Press of the People's Commissariat of the Navy of the USSR, Moscow, 1943)
This record consists of an English translation. This study was published in 1945, and the document is one of a series of 39 such studies of various aspects of the performance of the Soviet Navy during the war. Contains the original document in Russian. Topics include: frontline situation of the forces of northern defensive region on the coast of Varangerfjord and Sredniy and Rybachiy Peninsula; commander's concept and operational plan; decision of the commander, northern fleet, and plan of joint operations with Karelian front for the liberation of the Soviet far north; preparation for execution of the assigned mission; execution of the assigned missions; and organization of command and control for combat and the accomplishment of coordination.